Firm employment, exit, and growth in the food processing sector: Evidence from Ghana - Andam, Kwaw S.; Asante, Seth (International Food Policy Research Institute, 2018)
This paper uses data from a sample of 679 food processing firms in Ghana to estimate changes in employment by the food processing sector from 2014 to 2017, to analyze the determinants of firm exit during the same period, and to analyze the determinants of firm growth from the firm’s establishment up to 2017. In modeling the determinants of firm growth, the focus is on the effects of formal status as a food processing firm, which is defined in this paper as registration as a business for tax purposes and registration with the national food regulator, the Food and Drugs Authority (FDA).